Ischnura foylei sp. nov. (Odonata, Coenagrionidae) from the highlands of Sumatra - Kosterin, Oleg E. (Zootaxa, 2015)
Ischnura foylei sp. nov. is described from Indonesia, Sumatra, Jambi Province, Danau Gunung Tujuh (or Danau Sakti), a lake situated in an extinct volcanic crater, 1°41'15"S, 101°25'28"S, 1995 m a.s.l. Structurally it is close to I. senegalensis but larger and with differently shaped cerci in males and a more trilobate posterior lobe of the prothorax; males and androchromatic females have a unique colour pattern.